2015
DOI: 10.1007/s40864-015-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Metro Drivers Towards Design of Immediate Physical Environment and System Layout

Abstract: In this study, the authors examined attitudes of the Tyne & Wear (T&W) Metro drivers towards system design-related factors and their influence on the propagation of driver-related incidents. The system design features assessed include the position of running signals, visibility of different signal types, and platform location in relation to the travelling direction. The methodology based on data gathering through a self-administered questionnaire distributed among the drivers has been used. These data have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…While significant rail accidents are subject to extensive 189 reporting, it was unclear whether it would be possible to identify latent features of accidents, at both 190 organisational levels and beyond, in the type of reports generated for minor safety of the line 191 incidents, or whether these investigations focus more on surface-level features relating to unsafe acts 192 and their preconditions. Rjabovs and Palacin (2015) found that there was a tendancy not to attribute 193 systemic, physical or design factors to the causation of SPADs in a metro environment, and it is likely 194 that a similar issue might arise when looking at other types of rail transport. Therefore, this paper also 195 aimed to measure the quality and depth of the information contained in minor incident investigation 196 reports.…”
mentioning
confidence: 99%
“…While significant rail accidents are subject to extensive 189 reporting, it was unclear whether it would be possible to identify latent features of accidents, at both 190 organisational levels and beyond, in the type of reports generated for minor safety of the line 191 incidents, or whether these investigations focus more on surface-level features relating to unsafe acts 192 and their preconditions. Rjabovs and Palacin (2015) found that there was a tendancy not to attribute 193 systemic, physical or design factors to the causation of SPADs in a metro environment, and it is likely 194 that a similar issue might arise when looking at other types of rail transport. Therefore, this paper also 195 aimed to measure the quality and depth of the information contained in minor incident investigation 196 reports.…”
mentioning
confidence: 99%
“…This is the second largest urban rail system in the UK and the only one powered by an overhead DC 1500 V supply network. Further details on the T&W network can be found in [9][10][11][12]. The in-field eye-tracking experiment was designed as a naturalistic driving study.…”
Section: Methodsmentioning
confidence: 99%
“…In each trial only certain timeframes were analysed: 15 s before a full stop at a station and 10 s before a departure from a station. Previous research [11,12,14] suggested a relationship between a type of physical environment at a station and drivers' performance, which was selected as an avenue for this research. The arrival timeframes were selected to analyse potential effects of the built environment on selection of a stopping position, or distractions causing a dip in performance.…”
Section: Trials Designmentioning
confidence: 99%
“…Performance of metro systems and train delays have been studied by Marinov and Viegas [1], Rjabovs et al [2], Rjabovs and Palacin [3], Wales and Marinov [4], Dampier and Marinov [5], Darlton and Marinov [6], Rjabovs and Palacin [7], Rjabovs and Palacin [8], and Powell et al [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Rjabovs and Palacin concluded that drivers have good route knowledge that should in theory translate into near ideal timetable keeping if there are no other influences. One can claim that irregularities in a timetable causing conflicting movements and delays is one of the examples of such influence [3].…”
Section: Introductionmentioning
confidence: 99%